Gradient Boosting in Motor Insurance Claim Frequency Modelling - Clemente, Carina de Miranda (2023)
Clemente, C. D. M., Guerreiro, G. R. D., & Bravo, J. M. (2023). Gradient Boosting in Motor Insurance Claim Frequency Modelling. In CAPSI 2023 Proceedings (pp. 53-69). Article 5 (Atas da Conferência da Associação Portuguesa de Sistemas de Informação). Associação Portuguesa de Sistemas de Informação. https://doi.org/10.18803/capsi.v23.53-69 --- This research was funded by national funds through the FCT – Fundação para a Ciência e a Tecnologia, I.P., under the scope of the projects UIDB/00297/2020 and UIDP/00297/2020 -- Center for Mathematics and Applications -- (G. R. Guerreiro) and grants UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC) and UIDB/00315/2020 -- BRU-ISCTE-IUL -- (J. M. Bravo).